Pengembangan Paradigma Integrasi Ilmu: Harmonisasi Islam dan Sains dalam Pendidikan - Hidayat, Fahri (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2015)
Secularism that separates religion from mundane aspects, including science andknowledge, that appeared and applied in the West turned out to present themselves asa different face when applied in the Islamic world. In the West, secularism became areason for science breeding. Meanwhile, in the Islamic world, secularism actually triggerthe birth of science dichotomy that led to the neglect of science. In turn, the practiceof science dichotomy is precisely the cause of the deterioration of Islamic civilization.Muslim community has a different cultural history with the West. Historically, Islambecame the main driver of progress of science in the golden age. This is different withWestern history that marred by tensions between science and religion. Therefore, Islamiceducation should be developed in accordance with its integrative and nondichotomousculture. Therefore, religion and science in Islam is a unity. Epistemology of Islamiceducation is built by making sciences as part of its supporting pillars.